PENGARUH KECERDASAN SPIRITUAL, KECERDASAN EMOSIONAL, DAMPAK NEGATIF JEJARING SOSIAL DAN KEMAMPUAN BERPIKIR DIVERGEN TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Erwin Nurdiansyah (Journal of Educational Science and Technology (EST), 2016)
This study aims to describe and how much influence the spiritual intelligence, emotional intelligence to the learning outcomes of mathematics either directly or indirectly through the negative impact of social networking, and divergent thinking skills students learn. This type of research is ex-post facto nature of causality. This study population is students of class X SMA Se-District of Bontotiro Bulukumba the school year 2014/2015 as many as 765 with a sample size of 175. Engineering samples is done by using proportional stratified random sampling. The instrument used in this study were (1) Methods documentation for learning outcomes, (2) Scale spiritual intelligence, (3) Scale of emotional intelligence, (4) The scale of the negative impact of social networking, (5) Test divergent thinking skills. Data were analyzed with descriptive and inferential statistical methods SEM (Structural Equation Modeling). The results showed that: (1) Most of the students have spiritual intelligence is in the category of high emotional intelligence are in the high category, the negative impact of social networking are in the low category, divergent thinking skills are in high category and yield learning mathematics are in the high category ; (2) Directly spiritual intelligence positive and significant effect on the results of students' mathematics learning, indirectly positive effect but not significant to the results of students' mathematics learning through the negative impact of social networking and indirect positive and significant impact on the results of students' mathematics learning through capability divergent thinking. (3) Directly emotional intelligence positive and significant effect on the results of students' mathematics learning, indirectly positive effect but not significant to the results of students' mathematics learning through the negative impact of social networking and indirect positive and significant impact on the results of students' mathematics learning through capability divergent thinking.